Neonatal outcomes after fetal exposure to methadone and buprenorphine: national registry studies from the Czech Republic and Norway - Nechanská, Blanka; Mravčík, Viktor; Skurtveit, Svetlana; Lund, Ingunn Olea; Gabrhelík, Roman; Engeland, Anders; Handal, Marte (Addiction (Abingdon, England), 2018)
BACKGROUND AND AIMS: Opioid maintenance treatment (OMT) is recommended to opioid-dependent females during pregnancy. However, it is not clear which medication should be preferred. We aimed to compare neonatal outcomes after prenatal exposure to methadone (M) and buprenorphine (B) in two European countries. DESIGN: Nation-wide register-based cohort study using personalized IDs assigned to all citizens for data linkage. SETTING: The Czech Republic (2000-14) and Norway (2004-13). [Correction added after online publication on 26 April 2018: The Czech Republic (2000-04) corrected to (2000-14).] PARTICIPANTS: Opioid-dependent pregnant Czech (n = 333) and Norwegian (n = 235) women in OMT who received either B or M during pregnancy and their newborns. MEASUREMENTS: We linked data from health registries to identify the neonatal outcomes: gestational age, preterm birth, birth weight, length and head circumference, small for gestational age, miscarriages and stillbirth, neonatal abstinence syndrome (NAS) and Apgar score. We performed multivariate linear regression and binary logistic regression to explore the associations between M and B exposure and outcomes. Regression coefficient (β) and odds ratio (OR) were computed. FINDINGS: Most neonatal outcomes were more favourable after exposure to B compared with M, but none of the differences was statistically significant. For instance, in the multivariate analysis, birth weight was β = 111.6 g [95% confidence interval (CI) = -10.5 to 233.6 and β = 83.1 g, 95% CI = -100.8 to 267.0] higher after B exposure in the Czech Republic and Norway, respectively. Adjusted OR of NAS for B compared with M was 0.94 (95% CI = 0.46-1.92) in the Norwegian cohort. CONCLUSIONS: Two national cohorts of women receiving opioid maintenance treatment during pregnancy showed small but not statistically significant differences in neonatal outcomes in favour of buprenorphine compared with methadone.
Keywords: lineární modely; Registries; novorozenec; Infant, Newborn; logistické modely; výsledek těhotenství; Pregnancy; Humans; poruchy spojené s užíváním opiátů; Buprenorphine; Premature Birth; methadon; Apgar skóre; Infant, Small for Gestational Age; registrace; Neonatal Abstinence Syndrome; novorozenecký abstinenční syndrom; gestační stáří; opiátová substituční terapie; Female; mladý dospělý; dospělí; Opiate Substitution Treatment; Pregnancy Outcome; Opioid-Related Disorders; lidé; Pregnancy Complications; Stillbirth; Norway; Methadone; buprenorfin; Apgar Score; Analgesics, Opioid; Adult; samovolný potrat; ženské pohlaví; Male; opioid maintenance treatment; Linear Models; opioidní analgetika; těhotenství; Czech Republic; health registries; Young Adult; neonatal outcomes; komplikace těhotenství; prenatal exposure; narození mrtvého plodu; Česká republika; mužské pohlaví; předčasný porod; Abortion, Spontaneous; Norsko; Logistic Models; Gestational Age; methadone; hypotrofický novorozenec